A Generation System of Multiple Choice Questions Using Idioms with Multiple Component Keywords - Lee, Jae-Young; ., . (International Journal of Engineering and Technology, 2018)
In order to alleviate the burden for the time-consuming and tedious tasks to make multiple choice questions, we proposed the system that generates multiple choice questions from the sentence with multiple component keywords and then relocates the questions selected by an array with random numbers instead of random functions in order to reduce the relocation time, after the system searches for the group of informative sentence with multiple component keywords by using special idioms. In this paper, the idiom is the CRm type idiom that has several components at the right side of this idiom including in a main informative sentence. The next sentences consist of other informative sentences including the components keywords. To make multiple choice questions, the system randomly selects an informative sentence including a component keyword and it also converts the informative sentence into a question. The selected component keyword is used as the correct answer and the three other component keywords are used as distractors. To produce many different questions about the same contents with different positions of the question and items, the system uses a random number array to reduce the relocation time.Â Â